New applications of sustainable, scalable, standardized, and cost-effective human biomaterials for cell-based assays, tissue engineering, and regenerative medicine - Salzmann, Rebekka J. S.; Domazet, Sandra; Prado-López, Sonia; Kigili, Seyda; Neuhaus, Winfried; Brachner, Andreas; Egger, Gerda; Moroni, Lorenzo; Hackethal, Johannes (Frontiers in Bioengineering and Biotechnology, 2026)
Human-derived biomaterials offer several advantages over animal-derived or synthetic alternatives, including improved biocompatibility, ethical acceptability, sustainability, and clinical translatability. Here we present new applications of human placenta-derived materials – specifically HUMAN PLACENTA substrate, collagen type-I, and Laminin-111 – as 2D coating materials and 3D matrices for the cultivation of spheroids and adherent cells. Collagen type-I coatings supported colorectal cancer spheroid formation without the need for growth-factor supplementation. Lm-111 significantly enhanced NIH3T3 fibroblast adhesion compared with poly-L-lysine and rat-tail collagen type-I, performing comparably to bovine fibronectin. In a transwell blood–brain barrier model, HUMAN PLACENTA substrate coatings enabled confluent endothelial monolayers with transendothelial electrical resistance values not significantly different from the conventional human collagen type-IV/bovine fibronectin mixture. Across these in vitro models, placenta-derived materials performed comparably or better than conventional animal-derived and synthetic coatings, supporting robust cell viability, adhesion, and barrier formation. Due to their human origin, these biomaterials exhibit reduced biological complexity while enhancing biocompatibility and translational relevance. Therefore, they provide a sustainable, ethically acceptable alternative for advanced cell culture systems.